Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702204
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Fun

Abstract: Games are normally considered to be "fun", though recently there is growing interest in how gameplay can promote empathy and encourage reflection through "serious experience". However, when looking beyond enjoyment, it is not clear how to actually evaluate serious experience. We present an evaluation of four games that were submitted to a student game design competition; the competition challenged teams to design a game that inspired curiosity around human error and blame culture within the context of healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…In contrast, the final theme, where discomfort acted as a catalyst for reflecting on life, the universe and everything, is more concerned with 'enlightenment' i.e., where players reflected on themselves and what they were capable of, or on wider societal issues. As with previous work, it is clear that uncomfortable experiences can lead to reflection [e.g., 4,18,23]. However, while transformative reflection in games appears to be relatively rare [29], we did observe occasions where experiences led to significant changes in gameplay (e.g., P30 deciding to play through the game without killing Raiders) or in terms of understanding that extended beyond the game itself (e.g., P42 investigating how people to become murderers).…”
Section: How Do Uncomfortable Experiences Influence Player Engagement?supporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, the final theme, where discomfort acted as a catalyst for reflecting on life, the universe and everything, is more concerned with 'enlightenment' i.e., where players reflected on themselves and what they were capable of, or on wider societal issues. As with previous work, it is clear that uncomfortable experiences can lead to reflection [e.g., 4,18,23]. However, while transformative reflection in games appears to be relatively rare [29], we did observe occasions where experiences led to significant changes in gameplay (e.g., P30 deciding to play through the game without killing Raiders) or in terms of understanding that extended beyond the game itself (e.g., P42 investigating how people to become murderers).…”
Section: How Do Uncomfortable Experiences Influence Player Engagement?supporting
confidence: 66%
“…The previous section indicates how players experience moving moments and emotional challenge in games that are played for entertainment. Other research has also suggested that uncomfortable gameplay experiences can facilitate enlightenment, particularly when they cause empathy and increase understanding around a particular issue [1,18].…”
Section: The Value Of Discomfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, reflection is a crucial component of learning [7,14,41], where already a substantial body of work considers how games and gaming practice support learning [24,46,48]. Third, recent work has explored games to promote thought-provoking 'serious experiences' [27,37] to raise awareness or persuade. Some have pointed towards games as a means to facilitate transformative reflection [44], which could give way to attitudinal and behavioral change [19].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is particularly useful for drawing people's attention to important but difficult issues that they might naturally want to avoid. For instance, the game Nurse's Dilemma [20], where players take on the role of a nurse faced with a series of difficult decisions, has been used to invoke reflection on themes such as responsibility and blame within healthcare.…”
Section: Related Workmentioning
confidence: 99%